Accessment of the Phytochemicals, Proximate & Elemental Composition of Chrysophyllum Africanum (Udara) - OKERULU I. O.; OMUKU P.E; ONWUMELU H.A; OKOYE P.A.C. (Innovare Journal of Food Sciences, 2015)
The freshly ripen samples of Chrysophyllum africanum commonly known as udaraâ€ among the Igbos and belong to the family sapotacea were obtained from tree plants at Umukwa village in Awka, Anambra state. The phytochemical Analysis of the methanol, water, ethylacetate extracts,Â  proximate analysis and the evaluation of the elemental constituent of the fleshy edible part of the Chrysophyllum afracanum were carried out. The methanol, water and ethylacetateÂ  extractsÂ  gave a positive test for the presence of alkaloids, flavonoids, saponin while phenols and glycosides were absent. Tannin was present in the methanol and ethylacetate extracts but absent in water extract. The proximate analysis showed the following results; protein contents (6.42%), moisture contents (70.8%), crude fibre contents (2.6%), ash contents (2.4%), carbohydrates (14.28%), Vitamin C (4.549mg/100g), Vitamin A (0.01mg/100g). The elemental analysis gave values for the metals; Ca (16.0mg/kg) > Cr (2.0mg/kg) > Zn (3.2mg/kg) > Fe (0.46mg/kg).Â  The levels of Pb occurred at none detectable limit of the instrumentation.